The diffusion of circular services: Transforming the Dutch catering sector. (10th September 2020) - Greer, Rachel; von Wirth, Timo; Loorbach, Derk
Abstract: Alternative ways to provide services based on circular economy principles are facing the problem of diffusing beyond local experimentations in niches to become mainstream. This is the entry point for our case study examining niche experimentation in the form of circular catering as developed within the urban living lab BlueCity010 in Rotterdam, the Netherlands, and how it interacted with incumbent actors. This case sets itself against the background of the national policy program "Circular Netherlands in 2050" and larger socio-political efforts to accelerate the transition to a circular economy in the Netherlands. Through a stakeholder analysis and in-person interviews, qualitative data was extracted that helped to map the process of diffusion, the inherent power dynamics, and connecting mechanisms between niche and current regime actors. The results detail various manners through which niche and regime actors connect, including actions taken to facilitate the diffusion of circular catering and settings that created a favorable environment. Our findings also include quantitative values for indicators of success from a Dutch ministry (e.g. CO2 emissions range, percent of animal protein, reduction of food waste), which appear in their very preliminary stage to be on track for meeting their circularity goals within catering. Our research offers novel empirical insights into how to increase and scale cleaner production practices towards a circular economy through circular startups, summarized into 15 observed principles for connecting and integrating niche innovations to incumbent practices. Lastly, these observed practices are discussed in connection to sustainability transitions and in terms of their potential generalizability to cleaner procurement. Highlights: One pathway for innovation diffusion: connect niche ideas to regime organizations. To an extent, a setting favorable for diffusing a circular service can be created. 15 principles for integrating niche innovation to incumbent practice were observed. There are alternative thinkers within incumbent organizations: a regime-niche.